Analisis Konsep Disiplin, Kekuasaan dan Normalisasi Sosial dalam Pendidikan Melalui Pendekatan Teori Michel Foulcault - Sulistyowati, Dewi; Sukino, Arif (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This article aims to examine how the concepts of power, discipline, and social normalization in education are understood through the lens of Michel Foucault's theory. From a Foucauldian perspective, power is not merely repressive and centralized, but is rather diffuse, productive, and present in all social relations, including in educational practices. Through techniques of surveillance, evaluation, and the instillation of norms, education plays a strategic role in shaping subjects who are compliant with established social norms. This study employs a qualitative-descriptive method with a literature review approach, analyzing Foucault's major works and their implementation within the context of educational management in Indonesia. The findings indicate that educational practices function as an effective instrument of social control in shaping the consciousness, behavior, and identity of students.